The mathematical simulation of the process of interaction the aircraft’s crew with airfield lighting system - Шишков, О. Ф.; Дев’яткіна, С. С. (Proceedings of National Aviation University (archive), 2003)
The suggested mathematical model sets the quantitative connection between the airfield lighting system reliability and flight safety level during visual piloting stage. The designed model is suggested to be the base for normalizing and assessment of airfield lighting systems reliability measures